Optimized condition for grafting reaction of poly(butyl acrylate) onto oil palm empty fruit bunch fibre - Ibrahim, NA; Wan Yunus, WMZ; Abu‐Ilaiwi, FAF; Rahman, MZA; Ahmad, MB; Dahlan, KZM (Wiley, 2003)
Preparation of poly(butyl acrylate)-grafted oil palm empty fruit bunch fibre (OPEFB) has been successfully carried out using H2O2/Fe2+ as a redox initiator in aqueous solution. The effects of reaction temperature and period, as well as the amount of monomer, initiator and nitric acid, on the percentage of grafting were investigated. The percentage of grafting increases with amount of monomer and can be controlled by setting the appropriate reaction conditions. The maximum percentage of grafting (about 265%) was obtained when the reaction was carried out without acid under optimum conditions (reaction period: 2 h, reaction temperature: 55°C, amount of H2O2: 5.88 mmol) with 42.2 mmol of monomer. Mechanisms of grafting of butyl acrylate onto OPEFB were proposed. Characterization of the grafted OPEFB was done by Fourier-transform infrared spectroscopy and scanning electron microscopy. The thermal properties were studied by thermogravimetric analysis.